Rh-Catalyzed Asymmetric Hydroformylation: The Case of Substituted and Heterocyclic Olefins - Tewari, Tanuja; Khopade, Kishor V.; Chikkali, Samir H. (ChemCatChem, 2025)
Asymmetric hydroformylation (AHF) of prochiral alkenes is an efficient way to synthesize optically active aldehydes, which are versatile chiral building blocks for pharmaceuticals, agrochemicals, and other fine chemicals. The purpose of this review is to take stock of developments in the last decade and shed light on the understanding of the field of AHF. So far, most of the literature methods focused on the use of Rh-based catalysts, due to high catalytic activity and excellent chemoselectivity for the aldehydes. Several chiral phosphorus ligands have been successfully developed for Rh-catalyzed AHF reactions. This review examines the role of the substrate/olefins in AHF. Several different types of ``mono-substituted'' terminal olefins (functionalized/nonfunctionalized) with a variety of chiral ligands have been investigated, which show high activity and excellent ee of up to 99%. The AHF of ``di-substituted'' and ``tri-substituted'' olefins is rarely reported. This review summarizes the evolution of chiral ligands for AHF. It discusses the progress made in desymmetrizing hydroformylation. In addition, it highlights important developments in AHF carried out with and without syngas. These advances span a wide variety of alkenes. Additionally, the review offers future approaches in the field of AHF for the synthesis of optically active aldehydes.
Keywords: Asymmetric hydroformylation; Asymmetric transfer hydroformylation; Chiral ligands; Desymmetrizing hydroformylation; Substituted alkenes